Cerebral venous sinus thrombosis associated with hyperhomocysteinemia due to methylenetetrahydrofolate reductase homozygous gene mutation: A case report (Indian Journal of Case Reports, 2026)
Cerebral venous sinus thrombosis (CVST) is a rare but potentially life-threatening condition requiring a high index of suspicion for diagnosis. We report a case of a 20-year-old vegetarian male presenting with acute severe headache, vomiting, and papilledema, diagnosed with left transverse and sigmoid sinus thrombosis secondary to hyperhomocysteinemia caused by a homozygous methylenetetrahydrofolate reductase gene mutation. Treatment with anticoagulants, mannitol, therapeutic lumbar puncture, and vitamin supplementation led to significant clinical improvement and partial thrombus recanalization at 6 months. This case underscores the importance of considering genetic causes of hyperhomocysteinemia in young patients with CVST, even in populations with dietary risk factors such as vegetarianism.